PP43 Do microfinance initiatives improve women's health? A systematic review of women's empowerment interventions. (2nd September 2014) - Orton, LC; Pennington, A; Nayak, S; Whitehead, M; Petticrew, M; White, M; Sowden, A
Abstract : Background: There is a growing public policy focus on empowerment for individuals and communities, and a belief that this may also reduce health inequalities. Our theory-driven systematic review of observational evidence on pathways between control and health revealed that low female control/empowerment was associated with adverse health outcomes and reduced survival for girls and women. We conducted a systematic review to address the question: what is the impact on health-related outcomes of interventions to improve the level of control in the living environment, differentiated by socio-economic status, gender, or ethnicity? Findings on women's microfinance initiatives are presented here. Methods: Studies were identified by searching seven bibliographic databases, screening reference lists, consulting key informants and searching organisational websites. All types of experimental and quasi-experimental study designs addressing the review question were included. Two reviewers carried out screening, data extraction and quality appraisal; disagreements were resolved through discussion with the wider team. Narrative synthesis of study findings drew upon conceptual frameworks developed in our previous review of pathways and the levels (micro/meso/macro) at which interventions might operate. Results: From 17, 361 initial records we identified 10 studies (one cluster-randomised control trial and 9 quasi-experimental studies) that met our inclusion criteria and evaluated the impact of microfinance initiatives. The interventions operated at the meso/community-level, via women's empowerment, whilst also seeking to influence the macro/societal-level by raising the status of women. All were from low-to-middle income countries and targeted poor rural women. Nine of the 10 studies provided evidence of associations between participation in microfinance schemes and improvements in health-related outcomes (reduction in interpersonal violence against women and infant and child mortality, and increases in use of family planning methods and health services) when compared with non-participation. One study found a higher probability of women ever experiencing interpersonal violence among participants compared to non-participants. Conclusion: Results from the microfinance studies reveal the potential health impact of attempts to influence control in the living environment by this type of intervention; providing rare evidence of a reduction in gender and socio-economic inequalities in health by purposeful theory-based programmes. More than 5 million poor rural women in Bangladesh alone are involved in such programmes. As the renewed focus on microfinance schemes grows in the UK and across the world, there is a need to learn from these evaluations. Future intervention studies should employ a robust research design to examine control/empowerment outcomes as well as differential impacts on health and wellbeing.